Effects of doping atoms (Sb, Te, Sn, P and Bi) on the equilibrium shape of Mg2Si from first-principles calculations. Issue 44 (13th September 2016) - Wang, Hui-Yuan; Xue, Xue-Na; Xu, Xin-Yu; Wang, Cheng; Chen, Lei-; Jiang, Qi-Chuan
Abstract : Te and P are competitive modifiers to promote the appearance frequency of (100) facets on a Mg2 Si crystal. Abstract : The surface energies of Mg2 Si (100) and (111) facets doped with modifying elements (Sb, Te, Sn, P and Bi) are calculated using first-principles methods, aimed at investigating the effects of the incorporation of modifying elements on the morphological evolution of Mg2 Si. Based on the results of surface energy, the equilibrium shape of pure Mg2 Si is predicted to be an octahedron surrounded by {111} planes. With the incorporation of Te, Sn, P and Bi, the ratio between the surface energies of the (100) and (111) planes ( r ) drops compared with that of pure Mg2 Si, promoting the extension of the (100) facets and the contraction of the (111) facets on Mg2 Si grains. Accordingly, the trend in morphological evolution for Mg2 Si is from the initial octahedron composed of {111} planes to a truncated octahedron surrounded by {111} and {100} planes. The results also show that Te and P are more effective in promoting the appearance frequency of (100) facets on the Mg2 Si crystal and can be used as candidate modifiers to realize the artificial manipulation of the morphology of Mg2 Si into a truncated octahedron. The findings here provide new insights for understanding the morphological evolution of Mg2 Si induced by the incorporation of modifying elements, which contributes to guiding the development of new high-temperature-resistant light alloys.